ChemInform Abstract: Asymmetric Redox‐Annulation of Cyclic Amines. Issue 9 (February 2016) - Kang, YoungKu; Chen, Weijie; Breugst, Martin; Seidel, Daniel
Abstract: Regio‐divergent cyclizations of 1, 2, 3, 4‐tetrahydroisoquinoline or ‐2‐azacarbazole with chiral 4‐nitrobutyraldehydes lead to highly substituted polycyclic ring systems.